Design and fabrication of automatic foodstuff cutter / Muhammad Afiq Aiman Amat Norizam - Amat Norizam, Muhammad Afiq Aiman (2023)
Food cutters designed specifically for potatoes are devices that slice potatoes from fresh potatoes. It is now a competitive alternative to the standard cutting method in the modern world. This method involves fewer processing steps and is more dependable in terms of processing time, cleanliness, and safety [1]. This thesis presents a mobile model of the process of creating, producing, and analysis food cutting instruments, particularly potatoes. The target market and potential clients include occupied urban areas, restaurant employees, and Small and Medium Businesses (SMEs). This initiative aims to create machines that are less expensive and easier to automate than those already in use in the industry. The utility of fabrication and the availability of materials are taken into consideration when building machine prototypes. The prototype's final testing and performance, including the quantity of potatoes that can be chopped and the prototype's effectiveness, are measured. In order to compete with other products on the market, the design is thought to be able to chop a high number of potatoes while serving as a user- friendly kitchen equipment.